Dryland Grain Sorghum in Central Kansas - Warmann, Gerald W. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on dryland grain sorghum production in central Kansas.
MF575_1995_10
Keywords: MF575; Economics; Crops; MF